Allosensitization Following Bone Graft. Issue 8 (17th March 2017) - O'Sullivan, E. D.; Battle, R. K.; Zahra, S.; Keating, J. F.; Marson, L. P.; Turner, D. M.
Abstract : It is recognized that patients may become sensitized to donor‐specific HLA antigens as a result of previous antigenic exposures, classically through previous transplantation, pregnancy, or blood transfusion. We present an unusual case of a patient who unexpectedly developed a range of anti‐HLA antibodies following orthopedic surgery where a bone graft was deployed intraoperatively. We describe the case of a 52‐year‐old man awaiting a renal transplantation, undergoing elective orthopedic surgery requiring a small‐volume bone graft. His postoperative antibody profile was found to be substantially changed compared to his previous negative samples, with the presence of HLA‐DR, DQ, and DP specificities, at levels that would be likely to give a positive flow cytometry crossmatch and therefore according to local procedures required listing as unacceptable antigens for organ allocation. We perform a literature review of all previous cases of allosensitization following bone graft. This case is the first to demonstrate allosensitization following minor surgery with ;low‐volume bone graft. Previous evidence is very limited and pertains only to massive osteochondral surgery for trauma or malignancy, and is confounded by potential concomitant blood transfusion. Clinicians should be aware of the risk of allosensitization where bone grafts are used. Abstract : This unusual case describes allosensitization following minor surgery with a low‐volume bone graft.